2018
DOI: 10.1371/journal.pone.0190351
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the diet and gastrointestinal microbiota normalizes systemic inflammation and β-cell chemokine expression associated with autoimmune diabetes susceptibility

Abstract: Environmental changes associated with modern lifestyles may underlie the rising incidence of Type 1 diabetes (T1D). Our previous studies of T1D families and the BioBreeding (BB) rat model have identified a peripheral inflammatory state that is associated with diabetes susceptibility, consistent with pattern recognition receptor ligation, but is independent of disease progression. Here, compared to control strains, islets of spontaneously diabetic BB DRlyp/lyp and diabetes inducible BB DR+/+ weanlings provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 91 publications
(130 reference statements)
0
19
0
1
Order By: Relevance
“…A growing number of studies have supported the striking linking of altered microbiota composition with the onset of several different autoimmune disorders (Table 1). These include Type I diabetes (T1D) [16,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]; rheumatoid arthritis (RA) [54,55,56,57,58,59,60,61,62]; systemic lupus erythematosus (SLE) [63,64,65,66,67]; inflammatory bowel disease (IBD) encompassing Crohn’s disease (CD) and ulcerative colitis (UC) [68,69,70,71,72,73,74,75,76,77,78]; Behcet’s disease (BD) [79,80,81,82]; autoimmune skin conditions including vitiligo [83], psoriasis vulgaris [84,85,86,87,88], and atopic dermatitis [89,90,91,92,93,…”
Section: Microbiome Composition and Autoimmune Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of studies have supported the striking linking of altered microbiota composition with the onset of several different autoimmune disorders (Table 1). These include Type I diabetes (T1D) [16,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]; rheumatoid arthritis (RA) [54,55,56,57,58,59,60,61,62]; systemic lupus erythematosus (SLE) [63,64,65,66,67]; inflammatory bowel disease (IBD) encompassing Crohn’s disease (CD) and ulcerative colitis (UC) [68,69,70,71,72,73,74,75,76,77,78]; Behcet’s disease (BD) [79,80,81,82]; autoimmune skin conditions including vitiligo [83], psoriasis vulgaris [84,85,86,87,88], and atopic dermatitis [89,90,91,92,93,…”
Section: Microbiome Composition and Autoimmune Conditionsmentioning
confidence: 99%
“…Recently, Henschel [50] reported that the peripheral inflammatory state correlated with autoimmune diabetes susceptibility was kept under control following modulation of the diet and gastrointestinal microbiota. More specific, spontaneous diabetic BB DR lyp / lyp and diabetes inducible BB DR + / + weanings fed with a standard cereal diet presented a considerable pro-inflammatory transcriptional expression consistent with microbial antigen exposure.…”
Section: Microbiome Composition and Autoimmune Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies frequently use non-physiological concentrations of pro-inflammatory cytokines to mimic the autoimmune attack on isolated islets. However, there are only a few studies on the natural course of pancreas gene expression in prediabetes (Crevecoeur et al 2017, Henschel et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the results suggest that current clinical management of ENDO may compromise women with accompanying T1DM and thus, advocate for physicians to recognize patients with ENDO and T1DM co-morbidities for provision of appropriate and optimal care. Given increasing support for the role of specific diets in the promotion of a pro-inflammatory state that is associated with T1DM (Vaarala 2011, Knip et al 2012, van Bussel et al 2013 and ENDO (Saguyod et al 2018, it is prudent to consider dietary changes, which can significantly impact the intestinal microbiota, for management of co-morbid ENDO and T1DM (Henschel et al 2018). Similarly, the use of metformin for targeting co-morbid T1DM and ENDO may have value, given recent evidence for its efficacy in reducing T1DM (Bjornstad et al 2018, Cree-Green et al 2019 and hindering the progression of ENDO lesions and associated signaling pathways (Takemura et al 2007, Yilmaz et al 2010.…”
Section: Potential Therapeutic Complications In Co-morbid T1dm and Endomentioning
confidence: 99%